Jean Genet's vertical geographies: on travel, politics, and form. Issue 2 (3rd April 2021) - Brueton, Joanne
ABSTRACT: This article explores the travel writings of dissident, anti-nationalist French writer, Jean Genet (1910-86) and argues that they use the geometry of place to resist the violence of political cartography. Traversing diverse geographies, from the domestic (Chartres) to the distant (Palestine, Japan, and Vietnam), it focuses on how Genet's vertical signifiers reveal an oppressively monolithic vision of a homeland. Genet encourages the reader's microspection into the flattening orthodoxies of a native soil to make visible the exploitation of those without a home. This emphasis on verticality helps him delve into the 1970s Palestinian revolution, his geometric writing excoriating the demarcation lines of imperial rulers seeking to appropriate, know, and dominate a non-Western other. This article reads Genet's vertical travel in two ways: a microscope into the hierarchies of oppressed peoples; and a voyage into travel writing itself, a literary process of "unearthing" that locates home in a perennial departure.